Effect of Crop Protection Intensity and Nitrogen Fertilisation on the Quality Parameters of Spelt Wheat Grain cv. ‘Rokosz’ Grown in South-Eastern Poland - Edyta Bernat; Sylwia Chojnacka; Marta Wesołowska-Trojanowska; Dorota Gawęda; Ewa Kwiecińska-Poppe; Małgorzata Haliniarz (Agriculture)
Spelt wheat is one of the oldest wheats cultivated by humans. It is characterised by high nutritional values and is sought after by consumers. Additionally, it does not have high habitat and fertilisation requirements and is resistant to diseases. The aim of this study was to determine the effect of different levels of nitrogen fertilisation and the intensification of fungicide protection on the grain quality characteristics of spelt cv. ‘Rokosz’ grown under south-eastern Polish conditions. The present research showed that the intensification of fungicide crop protection and increasing the nitrogen dose from 70 to 130 kg ha−1 had a positive effect on the quality features of spelt grains. The highest protein, gluten and starch contents were found after four fungicide treatments. These parameters increased their values under the influence of fungicides. After the application of 130 kg ha−1, spelt wheat grain had the most favourable chemical composition, containing the most protein, gluten, soluble dietary fibre, insoluble dietary fibre and fat. It also had a positive effect on the Zeleny sedimentation index and the amino acid content of the grain. Due to the favourable response of the spelt cv. ‘Rokosz’ to intensified fungicide protection and nitrogen fertilisation, it should be recommended for cultivation in integrated technology.